Detectable reentrant circuits in localized microreentrant tachycardias in the era of ultra high-density mapping. (19th May 2022) - Mantovan, R; Solimene, F; Pelargonio, G; Cauti, F; Marinigh, R; Schillaci, V; Narducci, ML; Rossi, P; Aloia, A; Di Donna, P; Grifoni, G; Carbone, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Optimal criteria in clinical practice differentiating microreentrant atrial tachycardias (mAT) from macroreentrant atrial arrhythmias (MAT) have not yet been clarified. The use of multielectrode catheters and the recent development of ultra high-density mapping (UHDM) with automated features has improved our knowledge of mAT circuits and foci location. Purpose: In the present study, we systematically evaluated AT mechanisms in a large consecutive cohort of patients with MAT identifying the precise mAT circuits using the Rhythmia mapping system. Methods: Consecutive patients indicated for MAT ablation from January 2021 to November 2021 at 33 centers were prospectively included. All MATs were completely mapped in the left or right atrium by means of the Rhythmia mapping system and the 64-poles Orion basket catheter. For study purpose, a mAT was defined as an AT with slow continuous low fragmented potentials covering at least 50% of tachycardia cycle length (CL) in a small area (set as a circuit within < 1 cm2) and in a couple of closed splines of the Orion catheter and a centrifugal activation pattern to the remainder of the atria. The Lumipoint tool was systematically used to confirm EGM fragmentation inside this area. Data are reported as mean±SD. Results: One-hundred eighty-seven MATs were analyzed: 100 (53.7%) atypical left atrial flutter, 27 (14.3%) left AT and 60 (32%) right AT. A total of 7 MAT (prevalence of 3.7%) was identified as mATs (6 atypical left atrial flutter and 1 AT), with 5 out 7 with a previous history of AF ablation procedure. The percentage of atrial surface with a voltage level below 0.1 mV was 19±17%. The CL was 329±78ms. The electrical activity spanning the whole CL was detected by 2±0.6 pairs of close bipoles of the Orion catheter, and was actually confined to a region of 0.4±0.2cm2 with continuous highly fractionated potential covering 68±10% of the CL (longest component of fractionated EGM per spline=74±18% of the CL). Voltage level was 0.3±0.1mV at RF delivery site and 0.2±0.1mV at the site of longest duration of the fragmented potential, respectively. Targeted mAT activity was identified closer to PVs in three cases and at the mid portion of the anterior wall and at the roof in two cases each, respectively. In all cases a single shot RF delivery terminated each arrhythmia at targeted location. Consolidative RF ablations were then delivered in the adjacent area. No complication occurred. At three months follow-up all patients remained free from any AT recurrence. Conclusions: In this standard of care clinical experience with UHDM system, the prevalence of mAT seems to be higher than previously reported in literature. A technique based on mAT identification through a novel automated algorithm and matched area of electrogram fractionation captured by the Orion catheter may limit the extent of ablation needed.